Faktor-Faktor Yang Berhubungan Dengan Kejadian Tuberkulosis Paru Di Puskesmas Lubuk Alung Kabupaten Padang Pariaman - nova arikhman (Jurnal Kesehatan Medika Saintika, 2019)
Pulmonary tuberculosis is an infectious disease which is caused by TB bacteria (Mycobacterium Tuberculosis). The number of lung TB in Puskesmas health centers year 2018 with a total of suspect lung 491 people and BTA + as many as 76 people. The purposed of this research was to find out if there was a level of knowledge, nutritional status and smoking habits by the incidence of pulmonary tuberculosis patients in the region of Lubuk Alung Health Center in 2019. The research used descriptive analytic research with Cross Sectional study design. The research has conducted at the Lubuk Alung Health Center on June 26, 2019 to July 27, 2019. The sample was chosen through simple random sampling, it consisting 84 respondents.The results of the analysis used Chi-Square statistical test. The results of univariate analysis showed that more than half of the 62 (82.1%) respondents had positive smear pulmonary TB, more than half (61.9%) of respondents had abnormal BMI and more of half (64.3%) of respondents have smoking habits. Bivariate analysis did there was a significant relationship between the nutritional status with the incidence of Lung Tuberculosis ie Pvalue 0.026 <0.05 and there was a significant relationship between smoking habits with the incidence of Lung Tuberculosis namely Pvalue 0.014 <0.05 at the Lubuk Alung Health Center in 2019.Keyword: Knowledge Level, Nutritional Status and Smoking HabitBibliography: 11 (2011-2018).